Impact of plants upon soil structural genesis and dynamics - Bacq-Labreuil, Aurélie (2019)
Soils are a fundamental component of terrestrial ecosystems, and support a myriad of functions via interactions between their physical and biological properties, mediated by soil structure. Soil structure is dynamic, and modified by biotic factors including plant roots. The mechanisms involved include enmeshment, exudation and rhizodeposition of C-rich materials, which adhere soil particles and serve as substrate for microbes - which in turn can further structure the soil. The overall aim of this study was to determine the effects of vascular plants upon soil structural genesis. These interactions were determined in different contexts, using aggregate size-distribution profiling and X-ray Computed Tomography to visualise and quantify soil structure in situ. Using long-term field studies (50 y) on a sandy and a clay soil, it was shown that the degree of plant presence in a soil had substantial effects upon its structure. Perennial plants (grassland) significantly increased porosity, pore size diversity and pore connectivity, compared to bare fallow soil which decreased these characteristics. The addition of organic manure to an arable soil had essentially the same effect upon structure as grassland management, revealing the profound effect of addition of manure upon soil structure. Moreover, an initially bare-fallow soil apparently required at least 10 years since conversion to show a partial recovery of soil structure due to the presence of plants. Further investigation in controlled pot experiments revealed that contrasting soil textures (sandy vs. clayey) induced differential effects of plants upon soil structural genesis, both in terms of aggregate size distribution and in situ soil structural properties. Furthermore, it was found that different plant species growing in the same sandy-loam soil had differing effects on soil structural genesis and microbial community phenotype, relatable to their contrasting root architectures. The key overall conclusion is that plant effects upon soil structure are context dependent, contingent upon the inherent cohesiveness of the soil texture, the plant species involved, and time. The concept of ‘optimal pore-architecture’ was developed from these observations of the differential impact of plants depending on soil texture: plant responses appear to be modulated by the initial state of soil structure and inherent soil properties.